Desafios à atuação da coordenação pedagógica escolar em contextos emergentes - Silva, Ticiane Arruda da (2024)
This Doctoral research in Education is linked to the Research Line “LP2 – Public educational policies, educational practices and their interfaces”, of the Postgraduate program in Education at the Federal University of Santa Maria (UFSM), and is part of the list of productions of the Group of Studies and Research in Public Policies and Educational Management (Gestar/CNPq). The study has an epistemological basis in the analysis of public educational policies, from teacher training to political-pedagogical practices in the school context, with an emphasis on (Self) Narrative Biographies of school pedagogical coordinators in emerging contexts. Thus, the general objective was: to understand the challenges related to the performance of school pedagogical coordination in emerging contexts. And the specific objectives were: i) to analyze the historical genesis of public educational policies, with a view to the constitution, institutionalization, formation and performance of school supervision until the constitution of school pedagogical coordination; ii) recognize paradigmatic conceptions of school supervision action until the establishment of pedagogical coordination in the school context; iii) identify challenges and parameters for the performance of school pedagogical coordination in emerging contexts. Methodologically, the research is based on a qualitative approach, considering the perspective of hermeneutics, in which narrative letters based on discourse analysis were used. Based on the analysis of the theoretical-empirical support, and considering the problem and objectives of this research, the following thesis was constructed and defended: “The challenges related to the performance of school supervision in emerging contexts, are subsidies to build legal and theoretical-practical bases that transcend their nomenclature and non-critical and technical-scientific paradigmatic perspective, implying the resignification to “pedagogical coordination” according to the complexity of its functions in the school context under the aegis of a “distinct vision” of critical and democratic-participatory management”. The challenges posed to the performance of school pedagogical coordination in emerging contexts were identified as follows: “mediation function”; “support and monitoring of pedagogical work”; “ongoing training”; “dialogical and reflective attitude”; “material and human resources and adequate and appropriate infrastructure in the school context”; “participatory planning” and “shared management processes”. Such challenges do not have a logical or important sequence, precisely because they are intertwined and interconnected and dialogue with each other, complementing each other. They also highlight the need to articulate school work according to each reality and build mechanisms based on principles of democratic management (autonomy, participation, collectivity, transparency and decentralization of power). It is also noteworthy that the challenges related to the performance of school pedagogical coordination in emerging contexts are intense, diverse and polysemic, which in this research were constituted based on the contributions of the collaborator, following ethical and legal provisions. Therefore, this journey of painting and leaving impressions on a blank canvas comes to an end, highlighting the thesis that proposes a paradigmatic and purposeful change in the designation and performance of school supervision for pedagogical coordination, which also needs to occur through the rearticulation of public policies in the scenario of educational and school management processes, highlighting the conception of management, performance and profile of these professionals, as well as their functions in emerging contexts.